Language and necessity. On the concept of time in Plato - Escobar Moncada, Jairo Iván (Estudios de Filosofía, 2003)
The purpose of this essay is the interpretation of passage 37d5-7 in Plato’s Timaeus, in which it is stated that time is an conic mobile image of aion which remains in the one and which moves according to the number. The central thesis is that time is understood by Plato from the dimension of language (logos) and the dimension of necessity (anánké), which intercross in time. To do so, that concepts are briefly discussed; also, the way both participate in determining that which we call time. Likewise, a concept of aion is thought of as life, but free from the connotation of eternity introduced by the Christian tradition. Furthermore, it tries to show how the concepts of logos and anánké, language and necessity, are the concepts underlying all of his philosophy.